2010
DOI: 10.1163/001121610x504360
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the Copepod Calanus Sinicus Brodsky, 1962 (Copepoda, Calanoida, Calanidae) in Northern Coastal Waters of Taiwan During the Northeast Monsoon Period

Abstract: The calanoid copepod, Calanus sinicus is transported into Taiwanese waters during the northeast (NE) monsoon season, during which time cold waters make incursions into Taiwanese coastal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Our results support earlier laboratory and field studies that provide direct evidence of feeding interactions between marine snow and euphausiids (Dilling et al 1998, Dilling & Brzezinski 2004, ostracods and amphipods (Lampitt et al 1993b), as well as copepods (Steinberg 1995, Koski et al 2007, Chen et al 2010, Wilson & Steinberg 2010. A few studies provided, as we have here, indirect evidence of feeding interactions through close spatial associations between zooplankton and marine snow aggregates (Shanks & Edmondson 1990, Bochdansky & Herndl 1992, Green & Dagg 1997, Shanks & del Carmen 1997, Malkiel et al 2006.…”
Section: Trophic Interactions Between Marine Snow and Zooplanktonsupporting
confidence: 91%
“…Our results support earlier laboratory and field studies that provide direct evidence of feeding interactions between marine snow and euphausiids (Dilling et al 1998, Dilling & Brzezinski 2004, ostracods and amphipods (Lampitt et al 1993b), as well as copepods (Steinberg 1995, Koski et al 2007, Chen et al 2010, Wilson & Steinberg 2010. A few studies provided, as we have here, indirect evidence of feeding interactions through close spatial associations between zooplankton and marine snow aggregates (Shanks & Edmondson 1990, Bochdansky & Herndl 1992, Green & Dagg 1997, Shanks & del Carmen 1997, Malkiel et al 2006.…”
Section: Trophic Interactions Between Marine Snow and Zooplanktonsupporting
confidence: 91%
“…Laboratory experiments with C. helgolandicus demonstrated that, in general, males moulted to adult and died in culture sooner than the females (Mullin and Brooks 1967). Male Temora longicornis were less sensitive (exhibited slower swimming velocities) to the presence of food than females (Moison et al 2013) and gut fullness ratios were lowest in male Calanus sinicus (Chen et al 2010), indicating that male copepods simply do not forage or ingest as much food as females. Calanus finmarchicus (Ohman et al 2004) and Calanus pacificus (Ohman and Hsieh 2008) male mortality rates were explained by atrophied mouth-parts and reduced feeding rates of adult males, leading to an exhaustion of lipid reserves.…”
Section: Comparing Mortality Rates Between Sexesmentioning
confidence: 97%
“…This paper aims to elucidate mortality rates together with attribution to the causes, and to explore the temporal dynamics of the mortality of the copepod species Calanus helgolandicus. This temperate copepod, inhabiting the North Eastern Atlantic and fringing shelves, is experiencing an expanding distribution which has been linked to various factors, including environmental warming (Chust et al 2014). It is an important contributor to the zooplankton biomass in these regions (Beaugrand et al 2003(Beaugrand et al , 2009Bonnet et al 2005), and is considered an important prey source for commercially important fish species (Heath 2007).…”
mentioning
confidence: 99%
“…In laboratory experiments with three types of prey, namely, cryptophytes, haptophytes, and diatoms, females of the copepod Acartia tonsa preferred diatoms, while males preferred cryptophytes (Ismar et al, 2018). For C. sinicus, an analysis of gut contents reported that females consumed more diatoms than males (Chen et al, 2010). Methods other than chl-a measurement may produce higher ingestion rates for C. sinicus males on potential prey than are reported in this paper.…”
Section: Developmental and Sexual Differencesmentioning
confidence: 44%